2000
DOI: 10.1007/s001980070052
|View full text |Cite
|
Sign up to set email alerts
|

Low Vitamin D Levels in Outpatient Postmenopausal Women from a Rheumatology Clinic in Madrid, Spain: Their Relationship with Bone Mineral Density

Abstract: To evaluate a possible relationship between vitamin D levels and bone mineral density (BMD) and the prevalence of hypovitaminosis in a population of postmenopausal women from a rheumatologic outpatient clinic in Madrid, Spain, 171 postmenopausal women (aged 47-66 years) divided into two groups (osteoporotic and nonosteoporotic, according to WHO criteria) were studied between November and June. Liver and kidney function were normal in all subjects. Serum parathyroid hormone (PTH) and calcidiol levels were deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(53 citation statements)
references
References 19 publications
5
45
0
3
Order By: Relevance
“…This state of calciferol insufficiency is replicated in Spain, with results which we show in table 1 [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] . The interlaboratory variation in the different methodologies used makes a rigorous comparison difficult, but the table illustrates clearly that, in spite of a theoretical climatological ease of vitamin D synthesis in Spain, the levels are similar to, or even lower than those reported for central Europe or Scandinavia, as has been described in earlier works 39 .…”
Section: State Of Vitamin D Insufficiency In Spainmentioning
confidence: 55%
“…This state of calciferol insufficiency is replicated in Spain, with results which we show in table 1 [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] . The interlaboratory variation in the different methodologies used makes a rigorous comparison difficult, but the table illustrates clearly that, in spite of a theoretical climatological ease of vitamin D synthesis in Spain, the levels are similar to, or even lower than those reported for central Europe or Scandinavia, as has been described in earlier works 39 .…”
Section: State Of Vitamin D Insufficiency In Spainmentioning
confidence: 55%
“…Previous studies have suggested that this may be a common occurrence (Bettica et al, 1999;Aguado et al, 2000). The explanation for the impaired PTH response is not readily apparent.…”
Section: Discussionmentioning
confidence: 94%
“…25-Hydroxyvitamin D insufficiency has been commonly described in the institutionalized older population of the northern hemisphere, but it has recently been proposed that insufficiency may indeed be more common in the general population than previously thought (Chapuy et al, 1996(Chapuy et al, , 1997bJacques et al, 1997;Bettica et al, 1999;Aguado et al, 2000;Inderjeeth et al, 2000;Oliveri et al, 2004). Combination calcium and vitamin D are commonly given for the treatment of osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that osteoporosis patients are usually prescribed oral and lower doses of NGB could explain why these patients are less concerned about jaw osteonecrosis. NGBs inhibit osteoclast activity but also have antiangiogenic effects, and, once incorporated into the bone, they are barely eliminated (7).…”
Section: To the Editormentioning
confidence: 99%